HaloTag is an effective expression and solubilisation fusion partner for a range of fibroblast growth factors - Sun,Changye; Li,Yong; Taylor,Sarah E.; Mao,Xianqing; Wilkinson,Mark C.; Fernig,David G. (PeerJ, 2015)
The production of recombinant proteins such as the fibroblast growth factors (FGFs) is the key to establishing their function in cell communication. The production of recombinant FGFs in E. coli is limited, however, due to expression and solubility problems. HaloTag has been used as a fusion protein to introduce a genetically-encoded means for chemical conjugation of probes. We have expressed 11 FGF proteins with an N-terminal HaloTag, followed by a tobacco etch virus (TEV) protease cleavage site to allow release of the FGF protein. These were purified by heparin-affinity chromatography, and in some instances by further ion-exchange chromatography. It was found that HaloTag did not adversely affect the expression of FGF1 and FGF10, both of which expressed well as soluble proteins. The N-terminal HaloTag fusion was found to enhance the expression and yield of FGF2, FGF3 and FGF7. Moreover, whereas FGF6, FGF8, FGF16, FGF17, FGF20 and FGF22 were only expressed as insoluble proteins, their N-terminal HaloTag fusion counterparts (Halo-FGFs) were soluble, and could be successfully purified. However, cleavage of Halo-FGF6, -FGF8 and -FGF22 with TEV resulted in aggregation of the FGF protein. Measurement of phosphorylation of p42/44 mitogen-activated protein kinase and of cell growth demonstrated that the HaloTag fusion proteins were biologically active. Thus, HaloTag provides a means to enhance the expression of soluble recombinant proteins, in addition to providing a chemical genetics route for covalent tagging of proteins.
Keywords: Fibroblast growth factor; Recombinant protein expression; HaloTag; Fusion protein